Apples of Gold in Pictures of Silver: Honoring the Work of Leon R. Kass - Levin, Yuval; Merrill, Thomas W.; Schulman, Adam (Lexington Books, 2012)
Leon R. Kass has been helping Americans better understand the human condition for over four decades_as a teacher, writer, scholar, public champion of the humanities, and defender of human dignity. From bioethics to civic education, from interpreting the Bible to weighing the moral implications of modern science, Kass has offered wisdom, guidance, and instruction. In this volume, fifteen of Kass's admirers, including students, colleagues, and friends, honor his work by reflecting on the broad range of subjects to which he has devoted his life's work. Some of the essays offer interpretations of great works of literature and philosophy from Homer, Sophocles, and Plato to Rousseau, Franklin, Jane Austen, Hawthorne, and Henry James. Others examine the significance of Leon Kass's work as a bioethicist and Chairman of the President's Council on Bioethics and as an interpreter of the Book of Genesis. The essays collected in Apples of Gold in Pictures of Silver offer a sense of the breadth of Kass's interests and insights and of the influence he has had on generations of scholars. The reader is further acquainted with the career of Leon R. Kass by a biographical introduction and a comprehensive listing of his published writings and the courses he has taught.